2015
DOI: 10.4269/ajtmh.15-0051
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Mansonella perstans Filariasis in Rural Senegal

Abstract: Abstract. Large parts of African and American countries are colonized by Mansonella, a very common but poorly described filarial nematode. Bloodsucking flies of the genus Culicoides are suspected to be the vector of Mansonella perstans, but no study in Senegal has confirmed that Culicoides can transmit the parasite. Designed specific real-time quantitative polymerase chain reaction (qPCR) can be used to identify microfilaria in stained blood smears. This study was performed in July and December 2010 in the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…In this work, the prevalence was independent of gender and age groups but was dependent on living area. The prevalence of M. perstans was highest in rural area; this finding is in conformity with other reports by Bassene et al [24] in Senegal and Debrah et al [25] in Ghana. Indeed, it is known that high prevalence of M. perstans occurs mainly in areas where tropical forests alternate with large swamps and open ground [2].…”
Section: Discussionsupporting
confidence: 92%
“…In this work, the prevalence was independent of gender and age groups but was dependent on living area. The prevalence of M. perstans was highest in rural area; this finding is in conformity with other reports by Bassene et al [24] in Senegal and Debrah et al [25] in Ghana. Indeed, it is known that high prevalence of M. perstans occurs mainly in areas where tropical forests alternate with large swamps and open ground [2].…”
Section: Discussionsupporting
confidence: 92%
“…Identification of these infections is often complicated by co-infection with other infective agents. Bassene et al analyzed patients infected only with M. perstans nematodes and concluded that these infections had little pathogenicity because infected persons were usually asymptomatic ( 5 ). Therefore, we considered as relevant identification of patients for whom other infections were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Culicoides‐ borne pathogens (Diptera: Ceratopogonidae) in the Afrotropical region are of interest because of major recent outbreaks affecting livestock (Mellor et al ., ; Mullen, ; Purse et al ., ; Carpenter et al ., ) and human populations (Agbolade et al ., ;Simonsen et al ., ; Bassene et al ., ; Debrah et al ., ). For example, in the last 20 years, African horse sickness outbreaks have been recorded in South Africa (Venter et al ., ), Senegal (Diouf et al ., ) and Namibia (Scacchia et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…For example, in the last 20 years, African horse sickness outbreaks have been recorded in South Africa (Venter et al ., ), Senegal (Diouf et al ., ) and Namibia (Scacchia et al ., ). Recently in West and Central Africa, high prevalence rates of Mansonella perstans were recorded in Culicoides specimens and human populations (Simonsen et al ., ; Bassene et al ., ; Debrah et al ., ). However, there have been few studies on the Culicoides fauna of the Afrotropical region.…”
Section: Introductionmentioning
confidence: 98%